Coordinated degradation of replisome components ensures genome stability upon replication stress in the absence of the replication fork protection complex. - Laura C Roseaulin; Chiaki Noguchi; Esteban Martinez; Melissa A Ziegler; Takashi Toda; Eishi Noguchi (PLoS Genetics)
The stabilization of the replisome complex is essential in order to achieve highly processive DNA replication and preserve genomic integrity. Conversely, it would also be advantageous for the cell to abrogate replisome functions to prevent inappropriate replication when fork progression is adversely perturbed. However, such mechanisms remain elusive. Here we report that replicative DNA polymerases and helicases, the major components of the replisome, are degraded in concert in the absence of Swi1, a subunit of the replication fork protection complex. In sharp contrast, ORC and PCNA, which are also required for DNA replication, were stably maintained. We demonstrate that this degradation of DNA polymerases and helicases is dependent on the ubiquitin-proteasome system, in which the SCF(Pof3) ubiquitin ligase is involved. Consistently, we show that Pof3 interacts with DNA polymerase ε. Remarkably, forced accumulation of replisome components leads to abnormal DNA replication and mitotic catastrophes in the absence of Swi1. Swi1 is known to prevent fork collapse at natural replication block sites throughout the genome. Therefore, our results suggest that the cell elicits a program to degrade replisomes upon replication stress in the absence of Swi1. We also suggest that this program prevents inappropriate duplication of the genome, which in turn contributes to the preservation of genomic integrity.